Analisis Efek Merger Terhadap Kinerja Perusahaan Pada PT. Bank Syariah Indonesia - Fernanda, Dedi; Thahirah, Khadijah Ath (Universitas Dharma Andalas, 2024)
Abstract This research aims to compare how companies perform before and after the merger. The object of this research is a sharia commercial bank that has carried out a merger, namely a merger between 3 sharia commercial banks to become Bank Syariah Indonesia. The research period is 2 years before the merger (2019-2020) and two years after the merger (2021-2022). The financial performance compared is Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Current Ratio (CR), Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR) and Cost to Income Ratio (CIR). The difference test uses a paired sample t-test in SPSS 25. The results of the paired sample t-test show that the overall ratios compared are no different before and after the merger. Abstrak Penelitian ini bertujuan membandingkan bagaimana kinerja perusahaan sebelum dan sesudah dilakukan merger. Objek penelitian ini adalah bank umum syariah yang pernah melakukan merger yaitu merger antara 3 bank umum syariah menjadi Bank Syariah Indonesia. Periode penelitian adalah 2 tahun sebelum merger (2019-2020) dan dua rahun setelah merger (2021-2022). Kinerja keuangan yang dibandingkan adalah Return on Asset (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Current Ratio (CR), Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR) dan Cost to Income Ratio (CIR). Uji beda menggunakan paired sampel t-test pada SPSS 25. Hasil paired sampel t-test menunjukkan bahwa keseluruhan rasio yang dibandingkan tidak terdapat perbedaan sebelum dan sesudah dilakukan merger.